Innovative and Hybrid Technologies for Wastewater Treatment and Recycling - Alam, Pervez; Khan, Afzal Husain; Américo-Pinheiro, Juliana Heloisa Pinê [UNESP]; Ahmad, Kafeel (Taylor & Francis, 2024)
Innovative and Hybrid Technologies for Wastewater Treatment and Recycling investigates the biological and non-biological features of the treatment process for wastewater and emphasizes the benefits that these aspects bring for sustainable engineering. It discusses several approaches that are based on biological and non-biological processes and examines the fundamental principles, practical applications, current achievements, future aspects, and associated limits. Further, it provides a wide range of innovative research on the treatment of wastewater, as well as the applications in the treatment, remediation, and pollution prevention processes. •Explains the principles and concepts of the most recent and innovative treatment processes for wastewater remediation. •Examines emerging nanofiber technology for the purification of wastewater. •Provides an overview of the most cutting-edge environmentally friendly technologies.